The Future of Data Efficiency: What is Active Learning in Medical AI? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Introduction: The Data Bottleneck in Digital Health Artificial Intelligence (AI), particularly deep learning, has demonstrated transformative potential ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine